Developing a feeding assay system for evaluating the insecticidal effect of phytochemicals on Helicoverpa armigera - Mohite, Sharada D.; Patil, Yogita P.; Nichit, Vikram J.; Joshi, Rakesh S. (Jove-Journal of Visualized Experiments, 2023)
Helicoverpa armigera, a lepidopteran insect, is a polyphagous pest with a worldwide distribution. This herbivorous insect is a threat to plants and agricultural productivity. In response, plants produce several phytochemicals that negatively impact the insect's growth and survival. This protocol demonstrates an obligate feeding assay method to evaluate the effect of a phytochemical (quercetin) on insect growth, development, and survival. Under controlled conditions, the neonates were maintained until the second instar on a pre-defined artificial diet. These second-instar larvae were allowed to feed on a control and quercetin-containing artificial diet for 10 days. The insects' body weight, developmental stage, frass weight, and mortality were recorded on alternate days. The change in body weight, the difference in feeding pattern, and developmental phenotypes were evaluated throughout the assay time. The described obligatory feeding assay simulates a natural mode of ingestion and can be scaled up to a large number of insects. It permits one to analyze phytochemicals' effect on the growth dynamics, developmental transition, and overall fitness of H. armigera. Furthermore, this setup can also be utilized to evaluate alterations in nutritional parameters and digestive physiology processes. This article provides a detailed methodology for feeding assay systems, which may have applications in toxicological studies, insecticidal molecule screening, and understanding chemical effects in plant-insect interactions.

Mechanistic insights in the role of trehalose transporter in metabolic homeostasis in response to dietary trehalose - Chaudhari, Bhagyashri Y.; Nichit, Vikram J.; Barvkar, Vitthal T.; Joshi, Rakesh S. (G3-Genes Genomes Genetics, 2026)
Trehalose is the major sugar in insect hemolymph and plays a diverse role. Its level is regulated by the dynamics of biosynthesis and distribution by sugar transporters. The metabolic balance between trehalose synthesis and uptake remains poorly understood, despite its critical role in homeostasis. Here, we examined the role of the putative gut-specific sugar transporter, HaST46, in regulating trehalose levels in Helicoverpa armigera, a model Lepidopteran pest. Analysis of publicly available transcriptomics, proteomics data, and qRT-PCR study suggests that HaST46 showed localization in the posterior midgut and its expression alters in response to dietary contents. The liquid chromatography-mass spectrometry (LC-MS) analysis of HaST46 overexpressing Sf9 cells indicated that trehalose transport is preferred over glucose. HaST46 expression was found to be modulated tissue-specific manner in response to dietary trehalose availability. Furthermore, trehalose synthesis genes were found to be downregulated in the case of a 50 mM trehalose diet. This suggests that a potential increase in exogenous trehalose uptake may attenuate its endogenous synthesis. HaST46 overexpression and silencing lead to altered trehalose levels in the insect, while also having impact on trehalose metabolizing enzymes. Overall, our findings reveal the role of gut predominant sugar transporter, HaST46, in metabolic fine-tuning between exogenous trehalose uptake and endogenous synthesis.
Keywords: gut; Helicoverpa armigera; Metabolism; sugar uptake; transporters; trehalose